Pregnancy at 40 years Old and Above: Obstetrical, Fetal, and Neonatal Outcomes. Is Age an Independent Risk Factor for Those Complications? - Bouzaglou, Ana; Aubenas, Ines; Abbou, Hind; Rouanet, Stephanie; Carbonnel, Marie; Pirtea, Paul; Ayoubi, Jean Marc Bernard (Frontiers in Medicine, 2020)
Objectives: Maternal age has been increasing for several decades with many of these late pregnancies between 40 and 45 years old. This is explained by the societal evolution marked by a constantly increasing use of controlled contraception. Late marriage and second marriages are also becoming more frequent. The main objective of this study is to assess whether maternal age is an independent factor of obstetric, fetal and neonatal complications. Patients and methods: A monocentric, French study "exposed-unexposed" was conducted during 11 years in a maternity level IIB. Maternal and perinatal outcomes were studied using univariates and multivariate analysis. We compared women aged 40 and above in a 1:1 ratio with women of 25-35 years old. Results: 1982 women were 40 or older (mean age: 41.9) on the day of their delivery and compared to other 1982 women who were aged between 25 and 35 years old (mean age: 30.7) Preeclampsia, gestational diabetes, were significantly higher in the study group (4.6% VS. 1.5% and 14.5% vs. 6.9% respectively, p < 0.001). We found also a significant difference for gestational hypertension (3.1% vs. 1.1% p<0,001), preterm birth (10.4% vs. 6.5% p<0.001) and cesarean (16.6% vs.5.4% for scheduled cesarean, and 50.4% vs. 13.9% for emergency cesarean, p<0.001). These results were also significantly different in multivariate analysis Among patient aged 40 years and above, we found a significant difference for preeclampsia and preterm delivery when they had another risk factor such as twin pregnancy or ART. Conclusion: A pregnancy after 40 years old is possible today as far as the risk factors are controlled and that the obstetrician is aware. However, they have a significantly higher risks of cesarean, preterm delivery, pre-eclampsia, gestational diabetes, and fetal death in utero (FDIU). It is therefore the responsibility of the obstetrician to inform correctly these women in a detailed way, to reassure them and to adapt the monitoring of their pregnancy accordingly.